Effect of Packaging and Modified Atmosphere on the Shelf Life of Rambutan (Nephelium lappaceum) I - Mohamed, Suhaila; Othman, Eshah (1988)
Rambutans undergo rapid darkening and dehydration of the skin in 72 hours or less when stored unwrapped at ambient temperature. Skin colour, firmness and weight of rambutans could be effectively preserved by low temperature storage, packagings and modifying the storage atmosphere. Low temperature storage at SOc prolonged the shelf life of fresh unwrapped rambutans to 6 days. Low permeability packaging (polyethylene rigid containers) together with low temperature storage extended the shelf life further to 18 days. Increasing the initial concentration of carbon dioxide to an optimum level of 7% at SOc effectively suppressed respiration offresh rambutan and prolonged the shelf life to nearly a month. Total absence of oxygen (as with vacuum packages) was detrimental to the shelf life offresh rambutan, since the fruit was unable to respire normally. A good co"elationship was found between weight loss of rambutan, darkening of skin and frimness of the fruit. The post harvest deterioration of rambutans was found to be mostly physiological.